2013
DOI: 10.2174/13895575113136660100
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol Cytotoxicity and Its Relation to Oxidative Stress

Abstract: Haloperidol (HP) is used for the symptomatic treatment of psychosis, manic phases, hyperactivity, aggressiveness, and acute delirium. Long-term use leads to various adverse side effects, especially to severe impairment of extrapyramidal nerve tracts and in particular, altered QT interval and increased incidence of arrhytmias. It is believed that cytotoxicity of HP and its metabolites is responsible for both neurotoxicity and cardiotoxicity. Extrapyramidal and cardiac adverse side effects may be explained by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…It has been hypothesized that SGAs may have a neuroprotective effect, either increasing the expression of neurotrophic factors (41) or stimulating neurogenesis (42) or interacting with and increasing the activity of N-methyl-D-aspartate glutamate receptors (43). Conversely, the excessive reduction in cortical GM observed in patients treated with FGAs may be attributable to a direct neurotoxic effect secondary to oxidative stress and/or excitotoxic phenomena, which have been well documented in animals treated with haloperidol (44)(45)(46)(47)(48). It may also indicate a hypothetical lower capacity of FGAs to interfere with the natural pathophysiologic trajectory of the disease, which may also be reflected in the different impact on cerebral blood flow and metabolism of FGAs versus SGAs (49-55).…”
Section: Regression Of Mdd (Cpz-eqmentioning
confidence: 99%
“…It has been hypothesized that SGAs may have a neuroprotective effect, either increasing the expression of neurotrophic factors (41) or stimulating neurogenesis (42) or interacting with and increasing the activity of N-methyl-D-aspartate glutamate receptors (43). Conversely, the excessive reduction in cortical GM observed in patients treated with FGAs may be attributable to a direct neurotoxic effect secondary to oxidative stress and/or excitotoxic phenomena, which have been well documented in animals treated with haloperidol (44)(45)(46)(47)(48). It may also indicate a hypothetical lower capacity of FGAs to interfere with the natural pathophysiologic trajectory of the disease, which may also be reflected in the different impact on cerebral blood flow and metabolism of FGAs versus SGAs (49-55).…”
Section: Regression Of Mdd (Cpz-eqmentioning
confidence: 99%
“…13 HP is cytotoxic to primary hippocampal neurons. 14 It was demonstrated that it causes necrotic death rather than apoptotic.…”
Section: Introductionmentioning
confidence: 97%
“…19 Because of the high acceptance rate and low price, haloperidol became one of the most widely used antipsychotic medications, particularly for managing acute conditions. 20 Therefore, whether haloperidol increases the risk of mortality is a serious public health concern. Most pharmacoepidemiological studies have involved a specific patient group, such as elderly adults, dementia patients, 21,22 and schizophrenic patients.…”
mentioning
confidence: 99%